ASME 1978 Citrus Engineering Conference 1978
DOI: 10.1115/cec1978-2404
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Citrus Fibers

Abstract: Limited quantities of dried juice sacs have been produced commercially in Florida since the late 1950’s. Several citrus processors have been involved in this production at one time or another and one well known processor is currently producing relatively small but significant quantities. Workers at the University of Florida’s Agricultural Research and Education Center at Lake Alfred, as well as at the USDA’s Utilization Research Labs at Winter Haven, Florida and Pasadena, California have been advocating this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This value agreed with the reported OHC values of citrus husk: 4 to 5 g oil/g dry matter (22). It has been shown that other fruit fibres with similar WHC and OHC values are useful as emulsifiers for meat products and thickening or bodying agents (23). TEP and SDF were significantly influenced by the treatment followed for MPDF preparation ( Table 1).…”
Section: Resultsmentioning
confidence: 94%
“…This value agreed with the reported OHC values of citrus husk: 4 to 5 g oil/g dry matter (22). It has been shown that other fruit fibres with similar WHC and OHC values are useful as emulsifiers for meat products and thickening or bodying agents (23). TEP and SDF were significantly influenced by the treatment followed for MPDF preparation ( Table 1).…”
Section: Resultsmentioning
confidence: 94%
“…Citrus rinds and other byproducts of juice extraction are traditionally dried and commercialized for feed (Ferguson & Fox, 1978). Considerable attention has also been focused on the incidence of a number of noninfectious diseases common in civilized societies and attributed to low dietary fibre intake.…”
Section: Introductionmentioning
confidence: 99%